Morphological Study of the Versatile Anther Group in the Tribe Zingibereae (Zingiberaceae) - Chatchai NGAMRIABSAKUL (Walailak Journal of Science and Technology, 2011)
Scanning electron micrographs of anther development in Cautleya spicata (Sm.) Baker show that the appendages develop from the joint connective tissue where one end of the anther develops first, well before the other turns into the appendages. The anther with appendages is thus basifixed in a mature plant in Cautleya spicata while observation of Curcuma species reveals that the anther is dorsifixed, and the appendages are derived from the thecae of the anther. Mapping this characteristic of the anther in the six genera that possess versatile anther in Zingiberaceae, namely Camptandra, Cautleya, Curcuma, Laosanthus, Paracautleya and Roscoea, onto the molecular based phylogeny of the tribe suggests that the dorsifixed versatile anther of the Curcuma complex has been lost independently in Hitchenia, Smithatris and Stahlianthus, while the basifixed versatile anther has arisen independently in Camptandra and Cautleya/Roscoea.